Gendered positionality among Irish male primary teachers: the staff room as a site of performative masculinity. Issue 3 (3rd July 2018) - O'Keeffe, Suzanne; Deegan, Jim
Abstract : The concept of masculinities has traditionally been defined in terms of crises associated with boys' underachievement, the violence of homophobia, the under-representation of males in caring occupations, the rituals and discourses of laddism, and perceptions of disaffected and unrealised talent. Whereas the topic of masculinities has long been associated with warrants for distinctive and diverse male identities, it has a comparatively more recent history in the research on male Irish primary teachers as a particular social category. Two key findings are discussed in relation to performative masculinities – a form of strategic manoeuvring designed to exploit gender discourses, practices for control, power and privilege. First, the findings show the staffroom as a bellwether or highly developed locus for teacher socialisation through gendered discourses, events and actions. Second, the findings show nonsynchronous performative masculinities not only between male and female teachers but also with male colleagues. Therefore, it is argued that this frequently forgotten and neglected seam in the grand narrative of schools and schooling in Ireland needs to be more fully understood as a variable of quality, social justice and democratic practices across the full scope and sequence of the teacher continuum and as a prerequisite component in all teacher leadership programmes.